A Black communist in the freedom struggle : the life of Harry Haywood - Haywood, Harry, 1898-1985 (University of Minnesota Press, 2012)
Mustering out of the U.S. army in 1919, Harry Haywood stepped into a battle that was to last the rest of his life. Within months, he found himself in the middle of one of the bloodiest race riots in U.S. history and realized that he'd been fighting the wrong war - the real enemy was right here at home. This book is Haywood's eloquent account of coming of age as a black man in twentieth-century America and of his political awakening in the Communist Party. For all its cultural and historical interest, Harry Haywood's story is also noteworthy for its considerable narrative.